2020
DOI: 10.1371/journal.pbio.3000954
|View full text |Cite
|
Sign up to set email alerts
|

Primate phylogenomics uncovers multiple rapid radiations and ancient interspecific introgression

Abstract: Our understanding of the evolutionary history of primates is undergoing continual revision due to ongoing genome sequencing efforts. Bolstered by growing fossil evidence, these data have led to increased acceptance of once controversial hypotheses regarding phylogenetic relationships, hybridization and introgression, and the biogeographical history of primate groups. Among these findings is a pattern of recent introgression between species within all major primate groups examined to date, though little is know… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 134 publications
(193 reference statements)
6
84
0
Order By: Relevance
“…In each of these systems introgression has occurred relatively recently, as the common ancestor for each species group occurred no more than 15 million years ago. A notable exception is evidence for introgression across much deeper phylogenetic timescales among vascular plants (Pease et al, 2018) and primates (Vanderpool et al, 2020). In some species, there is also evidence that introgression has been a source of adaptive genetic variation that has helped drive adaptation (e.g., (Chen et al, 2018;Eberlein et al, 2019;Jones et al, 2018;Platt et al, 2019;Richards and Martin, 2017)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In each of these systems introgression has occurred relatively recently, as the common ancestor for each species group occurred no more than 15 million years ago. A notable exception is evidence for introgression across much deeper phylogenetic timescales among vascular plants (Pease et al, 2018) and primates (Vanderpool et al, 2020). In some species, there is also evidence that introgression has been a source of adaptive genetic variation that has helped drive adaptation (e.g., (Chen et al, 2018;Eberlein et al, 2019;Jones et al, 2018;Platt et al, 2019;Richards and Martin, 2017)).…”
Section: Introductionmentioning
confidence: 99%
“…The extent of gene exchange in nature has remained one of the most hotly debated questions in speciation genetics. Genomic data have revealed that introgression is common across taxa, having been identified in major groups such as fungi (Eberlein et al, 2019;Leducq et al, 2016;Tusso et al, 2019), vertebrates (Lamichhaney et al, 2015;Racimo et al, 2015;Schumer et al, 2018;Vanderpool et al, 2020), insects (Edelman et al, 2019;Lohse et al, 2015;, and angiosperms (Pease et al, 2018(Pease et al, , 2016. The evolutionary effects of introgression are diverse, and are determined by multiple ecological and genomic factors (Rhymer and Simberloff, 1996;Taylor and Larson, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, gene trees at individual loci can disagree with each other and with the species tree, a phenomenon known as gene tree discordance. While genomic data allow us to overcome many technical sources of discordance ( Delsuc et al, 2005 ; Dunn et al, 2008 ; Misof et al, 2014 ), discordance also has biological causes ( Degnan and Rosenberg, 2009 ), and remains a common feature of phylogenomic datasets ( Pollard et al, 2006 ; Fontaine et al, 2015 ; Pease et al, 2016 ; Novikova et al, 2016 ; Wu et al, 2018 ; Vanderpool et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 displays an example of a phylogenetic workflow inspired from ( 3 ) and described in details in the Results section. The main objective of this workflow is to analyse a phylogenomic dataset to infer a species tree and compare it to a reference tree.…”
Section: Introductionmentioning
confidence: 99%